Expressive Language Delay Related to Chromosome 7 Defect - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Genetic analysis in a boy aged 8 years 10 months with severe delay in expressive language and orofacial dyspraxia uncovered reciprocal duplications of the Williams-Beuren syndrome (WBS) locus at chromosome 7q11.23, in a report from the University of Alberta, and other centers in Canada, USA, and Spain.